Історія становлення та розвитку законодавства України про вищу освіту - Тимошенко, М.О. (Часопис Київського університету права, 2009)
В статье исследуются вопросы истории становления законодательства о высшем образовании в Украине в период с 1990 года по сегодня. Автором проводится анализ законодательства о высшем образовании, проводится периодизация его развития, исследуются позиции ученых о тенденциях развития законодательства о высшем образовании в Украине. Ключевые слова: образование, высшее образование, высшее учебное заведение, частное высшее учебное заведение, правовое регулирование высшего образования. In the article the questions of history of becoming of legislation are probed about higher education in Ukraine in a period from 1990 to on today. An author is conduct the analysis of legislation about higher education, a division into periods of his development is conducted, positions of scientists are probed about progress of legislation trends about higher education in Ukraine. Key words: education, higher education, higher educational establishment, private higher educational establishment, legal adjusting of higher education.